MAJOR TRENDS OF BIG INTERNATIONAL COMPANIES DEVELOPMENT IN A CHANGING WORLD - N. Y. Konina (Vestnik MGIMO-Universiteta, 2016)
Economic globalization and demographic changes as well rapidly changing technologies are the most important factors of the firm's environment. The rapid development of information technology radically changes the very essence of the creation of new value. The pace of technological change and innovations increases. In the most advanced sectors of global economy the knowledge is a key resource. The world economy has not finally recovered after the crisis of 2008-2009. The global economy his becoming more multicentre and the vector of economic power is shifting to China and India. The main actors and the anchor of today global economy are leading international companies (transnational corporations- TNCs). Several thousands of TNCs together with their value chain dominate the global economy. The economic power allows the largest TNCs significantly push the boundaries of the company. Globalization has changed external networks of TNCs, their corporate governance, corporate ownership as well transfer pricing schemes as well relations between the headquarter and its subsidiaries and affiliates. A remarkable feature of TNCs recent FDI flows is not Greenfield investment but mergers and acquisitions. Key features of TNC activities are defined by industry. A growing number of TNCs are changing their strategic activities, basing on the latest technology trends. The most important aspects of TNCs activities are linked to innovation, financial operations, advanced management technique, increase in intangible assets. Innovation activity of TNCs is shifting to Asia.